HUMAN SEXUALITY AND BREAST CANCER PATIENTS - Sheriff, Dhastagir Sultan; Manopriya, T.; Murali, U. (International Journal of Research -GRANTHAALAYAH, 2019)
Sexuality reflects a person’s personality. Cancer, regardless of its location can affect sexuality. Cancer and its treatment have a bio-psycho-social impact on a patient.3 Research has shown that poor physical health and emotional distress can affect sexual health.4 Cancer survivors were reported to have sexual problem after cancer therapy,5 following changes in body image. Materials and Methods: Subjects taken for the study were who had come for consultation regarding their physical health including sexual health. 65 subjects with breast cancer patients were included in the study. Informed consent was taken from the cases and it was approved by an Institute Ethics review Board attached to the institute. Basson’s sexual response cycle formed the basis for formulating worksheet given to the patients to record breaks in their sexual response cycle following a sexual encounter they had with their partners ( husbands).5 It takes into account the role of intimacy in understanding the women’s sexual response cycle and it is non-linear in nature. This makes the model suitable for studying sexual response cycle in women in health and disease. Based on the model the work sheet was created to understand the sexual response cycle of women with breast cancer, The Breaks in the sexual response cycle were found to be due to Biological inhibiting factors like body image, fatigue and drug therapy along with psychological factors like pain, anxiety and depression. The main motivators of sexual response were physical intimacy and care in these patients.